Looking at Shakespeare Theatrically with Reference to the Development of the Role of the Clown Character (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2019)
This article examines the development of the role of the clown character in Shakespearean drama with reference to the following four plays: The Merchant of Venice, As You Like It, Twelfth Night and King Lear. The article explores the historical, dramatic, material and cultural context in which the plays were written, and illustrates how it influenced Shakespeare's work and motivated him to develop the nature and dramatic function of the clown character in his plays. The article starts with a brief survey of the origins and the early function of the clown character on the English stage, in general, and in a number of early plays by Shakespeare. In this context, the article provides an analysis of the clown character in The Merchant of Venice, and examines how Shakespeare presented it in its traditional form which was already familiar to the Elizabethan audience. Moving on to As You Like It, which marks the beginning of the radical development of the character. The article discusses the new clown character which Shakespeare developed around the year 1600 when the actor Robert Armin joined Shakespeare's company, and claims that Shakespeare designed the whole part of Touchstone to suit the style and acting abilities of the new actor. The article analyses the dramatic nature and function of the new clown character, and underlines the different factors which influenced Shakespeare's development of the role. It moves on to investigate the clown character in Shakespeare's later plays trying to illustrate other developments of this character in Twelfth Night. It also brings into discussion the clown character in King Lear, a tragedy, to serve the purpose of comparison. The article shows, indirectly, the discrepancies of its different readings when we limit its analysis to the application of traditional literary methods which are usually applied to fiction neglecting the fact that they were written to be performed in front of a specific audience in a specific historical and cultural context. يهدف هذا البحث إلى دراسة تطور شخصية المهرج ودورها الدرامي في مسرحيات شكسبير بالإشارة إلى أريع مسرحيات تم اختيارها لأنها كتبت في الفترة التاريخية 1597-1606 وتُمثل كل منها مرحلة هامة في تاريخ تطور شخصية المهرج وهي: تاجر البندقية, كما تريدها, الليلة الثانية عشرة والملك لير.ويستعرض البحث السياق التاريخي والدرامي والمادي والثقافي الذي أحاط بعمل شكسبير في المسرح ويكشف كيف أثر هذا السياق على شكسبير ودفعه لتطوير صفات شخصية المهرج ودورها الدرامي في مسرحياته. يبدأ البحث بعرض موجز لأصول شخصية المهرج المسرحية ووظيفتها الدرامية على المسرح الإنكليزي بشكل عام, وفي عدد من المسرحيات الأولى التي كتبها شكسبير. وفي هذا الإطار, يقدم البحث تحليلاً لدور شخصية المهرج في مسرحية تاجر البندقية ويظهر كيف قدمها شكسبير للجمهور الإليزابيثي في شكلها التقليدي. ثم ينتقل إلى دراسة شخصية المهرج في مسرحية كما تريدها التي تمثل بداية التطور الجذري الذي أجراه شكسبير على هذة الشخصية ووظيفتها الدرامية. في عام 1600 انضم الممثل روبرت أرمين إلى فرقة شكسبير المسرحية مما جعل شكسبير يفصل ويوظف دور المهرجTouchstone فيها ليتناسب مع نوعية وإمكانيات الممثل الكوميدي الجديد. يدرس البحث شكل هذة الشخصية الدرامية الجديدة ووظيفتها متلمساً العوامل التي دفعت شكسبير باتجاه هذا التطوير. ثم يتابع البحث تحليل شخصية المهرج في مسرحيتي الليلة الثانية عشرة في محاولة لرصد تطورهذة الشخصية في أعمال شكسبير اللاحقة. كما يدرس البحث شخصية المهرج في مسرحية الملك لير التراجيدية لمتابعة شكلها ووظيفتها مقارنة مع مثيلاتها في المسرحيات الكوميدية السابقة. ويكشف البحث، بشكل غير مباشر، التباين في قراءة هذه المسرحيات عندما تعالج كنصوص أدبية تدرس من خلال تطبيق نظريات النقد الأدبي التقليدية متجاهلة كونها كتبت بالأساس لتعرض على خشبة المسرح وخاطبت جمهوراً محدداً ضمن إطار تاريخي وثقافي محددين.